Pubblicità, guerra e pace. Un’interpretazione della prospettiva kantiana - Perni, Romina (Filosofia, 2023)
The aim of the article is to unify in one reflection three central themes of Kantian political philosophy: war, peace and publicity. First, I would like to delimit the sphere in which this union is possible, trying to see how peace and war are linked to the concept of public law. Then, I will focus on the relationship between peace, war and the idea of republic. Peace is a duty originating in the purity of law, but Kant is also convinced that in a republic, in which citizens are involved in political decisions, they will prefer peace to war. What role can publicity as a legal principle play?